Pengaruh Lingkungan Keluarga dan Minat Belajar terhadap Indeks Prestasi Akademik Mahasiswa Program Studi Pendidikan Ekonomi STKIP Panca Sakti Bekasi - Rahman Putrie, Chientya Annisa (Lembaran Ilmu Kependidikan, 2020)
This study aims to determine and analyze (1) The influence of family environment on student achievement index. (2) Effect of interest in learning on student achievement index. This type of research is descriptive and associative research. The study population was students of Economic Education at the Faculty of Economics UNP registered in the semester July-December 2018 class 2015 to 2017, a total sample of 81 people used the Slovin formula, while the sample collection technique was carried out using Proportional Sampling. Data analysis using descriptive analysis and inductive analysis (inferential), namely the normality test, homogeneity test, multicollinearity test, and hypothesis testing using multiple regression analysis, F test, coefficient of determination and t test with ÃŽÂ± = 0.05. The results showed that (1) There is a significant influence between family environment on student achievement index, seen from the sig value of 0.042 <0.05. (2) There is a significant influence between learning interest towards student achievement index, seen from the sig value of 0.026 <0.05. (3) There is a significant influence between family environment and learning interest on student achievement index, seen from the sig value of 0,000 <0.05.